Optimizing Urban Logistics Through Electric Vehicle Integration - Munawar, Soviyan (Yayasan Sinergi Kawula Muda, 2024)
The transition to electric-based logistics has become increasingly vital in the pursuit of sustainable urban transportation. This study presents a narrative review of recent literature examining the efficiency, environmental impact, and policy dimensions of electric vehicle (EV) adoption in logistics. Drawing on peer-reviewed articles from Scopus and Google Scholar published between 2015 and 2024, this review employed systematic keyword searches and thematic analysis to synthesize research findings. It includes studies on route optimization algorithms, charging infrastructure, economic feasibility, and the social implications of EV integration. Results indicate that EVs can significantly reduce urban emissions, improve delivery efficiency, and lower long-term operational costs. Advanced optimization algorithms and well-distributed charging infrastructure are essential for system performance. Public policies, such as financial incentives and emission regulations, strongly influence adoption rates, especially in regions with supportive governance. Despite these benefits, barriers such as high initial costs, limited charging networks, and the need for skilled labor persist. This review concludes that effective electrification of logistics requires coordinated investments in technology, policy, and human capital. Future research should focus on longitudinal and cross-regional studies, real-world pilot implementations, and stakeholder-inclusive policy design. The adoption of EVs in logistics presents a critical pathway toward achieving global climate goals, urban livability, and sustainable economic development.